Pengobatan Melalui Metode Al-Qur’an dan As-Sunnah dalam Islam - Muhammad Nihaya; Muhammad Thufail Paewai (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This article discusses medical practices based on the teachings of the Al-Quran and As-Sunnah in Islam. Treatment using verses from the Koran and prayers taught in the hadith (As-Sunnah), has been an important part of Islamic medical tradition for centuries. This article attempts to explain the basic principles of treatment based on the Koran and Sunnah, as well as highlighting the differences and similarities between this approach and conventional medical treatment. This article also discusses treatment based on the Al-Quran and As-Sunnah which has become an important part of Islamic medical practice. Muslim scholars and medical experts emphasize the importance of maintaining a balance between conventional medical treatment and treatment based on the Al-Quran and As-Sunnah. These two approaches can complement each other and be part of efforts to cure disease. In the conclusion of the article, we highlight the need for a wise and informed approach to treatment based on the Qur'an and Sunnah, along with recognition of the important role of modern medical treatment. With proper understanding and sound knowledge, healing practices based on Islamic teachings can be a source of strength and hope for many individuals seeking healing.